Differential Growth Responses of Alternanthera philoxeroides as Affected by Submergence Depths - Jing, Shufang; Zhang, Xiaoping; Niu, Hangang; Lin, Feng; Ayi, Qiaoli; Wan, Binna; Ren, Xinyi; Su, Xiaolei; Shi, Shaohua; Liu, Songping; Zeng, Bo (Frontiers in Plant Science, 2022)
Global climate change has resulted in an increase in intensity and frequency of flooding, plants living in lowlands and shore areas have to confront submergence caused by flooding, submergence-tolerant plants usually respond by adopting either escape or quiescence strategies. While certain plants exhibit a changeover from escape strategy upon partial submergence to quiescence strategy under complete shallow submergence, it remains unknown whether plants completely submerged at different water depths would adjust their strategies to cope with the change in submergence depth. Alternanthera philoxeroides is an ideal species to explore this adjustment as it is widely distributed in flood-disturbed habitats and exhibits escape strategy when completely submerged in shallow waters. We investigated the responses of A. philoxeroides in terms of morphology, anatomy, and non-structural carbohydrate metabolism by conducting experiments using a series of submergence depths (0 m, 2 m, 5 m, and 9 m). During the submergence treatment, environmental factors such as light, dissolved oxygen, and temperature for submerged plants were kept constant. The results showed that A. philoxeroides plants submerged at depth of 2 m presented an escape strategy via fast stem elongation, extensive pith cavity development, and small biomass loss. However, the retarded stem elongation, reduced pith cavity transverse area, and increased biomass loss along the water depth gradient indicated that A. philoxeroides altered its growth response as water depth increased from 2 m to 9 m. It is found that the changeover of response strategies occurred at higher submergence depths (5 m to 9 m). Based on the results of our experiments, we demonstrated that water depth played an important role in driving the change in strategy. The water-depth-dependent growth performance of A. philoxeroides would benefit the species in habit exploration and exploitation. Further studies should focus on when plants are submerged in waters with different light climate and dissolved oxygen content, how water depths drive the response behaviors of the submerged plants.